Chenopodium ambrosioides L. do uso popular aos ensaios pré-clínicos: análise química, potencial anti-inflamatório e estudo da toxicidade - Jesus, Roberta da Silva (2019)
Chenopodium ambrosioides L., popularly known as Erva-de-Santa-Maria, is widely used in folk medicine against many diseases, as anti-inflammatory, healing, among others. In 2009, it was inserted in RENISUS, due to its wide popular use. The aim of this study was to perform the chemical characterization of the irradiated and non-irradiated extracts of C. ambrosioides L., as to elucidate the mechanisms of action involved in the possible anti-inflammatory activity of this species and to determine its safety through in vitro and in vivo assays. The chromatographic profile of the irradiated and non-irradiated extracts was obtained by HPLC-DAD, in order to compare their bioactivity and to verify possible changes in the chemical profile caused by gamma radiation. All samples presented the same qualitative chromatographic profile, but quantitative differences were found between the compounds identified in the extracts. The irradiated plant extract (IPE) showed an increase of canferol derivatives and quercetin derivatives about 20 times more than the other extract. All samples tested were effective in inhibiting LOX at 0.400 - 0.488 mg/mL. Regarding the nitric oxide radical, the non-irradiated plant extract (NIPE) presented the best elimination potential (IC50 value of 0.431 mg / mL). Samples were also evaluated for their toxicity and anti-inflammatory potential in RAW 264.7 macrophages, presenting a safe concentration up to 0.250 mg / mL and NIPE was the most effective in reducing NO in the cell assay (IC50 0.201 ± 0.029 mg / mL). The results obtained in the in vitro analysis appointed the non-irradiated extract for the in vivo study, since it presented a better bioactivity in the performed assays. Mass analysis revealed the presence of 6-hydroxycoumarin, p-coumaric acid, ferulic acid, quercetin-3-O-rutinoside, apigenin, quercitrin, quercitin and canferol. In the acute oral toxicity study, C. ambrosiodies extract was classified as safe (category 5) according to OECD guidelines. Administration of the extract at repeated doses (28 days) only increased AST enzyme activity in females treated with 50 mg / kg. Other toxicological parameters were not altered by extract administration (50-200 mg / kg) in males and females. C. ambrosiodes and B. serrata reduced ear edema induced by croton oil by 47.18 ± 4.59% and 34.23 ± 4.78% (by 1mg / ear), respectively. The same treatments also reduced croton oil-induced inflammatory cell infiltration (observed by myeloperoxidase activity) by 40.71 ± 14.71 for C. ambrosioides (1 mg / ear) and 35.93 ± 9.97% for B. serrata (1 mg / ear). The results obtained in the present study demonstrate the safety profile of C. ambrosioides and its potential as a topical anti-inflammatory agent in the treatment of inflammatory skin disorders, justifying its use in folk medicine.